Unloading of Right Ventricle and Clinical Improvement after Ultrasound-Accelerated Thrombolysis in Patients with Submassive Pulmonary Embolism. (1st July 2014) - Jain, Sachin Kumar Amruthlal; Patel, Brijesh; David, Wadie; Jazrawi, Ayad; Alexander, Patrick
Abstract : Acute pulmonary embolism (PE) can be devastating. It is classified into three categories based on clinical scenario, elevated biomarkers, radiographic or echocardiographic features of right ventricular strain, and hemodynamic instability. Submassive PE is diagnosed when a patient has elevated biomarkers, CT-scan, or echocardiogram showing right ventricular strain and no signs of hemodynamic compromise. Thromboemboli in the acute setting increase pulmonary vascular resistance by obstruction and vasoconstriction, resulting in pulmonary hypertension. This, further, deteriorates symptoms and hemodynamic status. Studies have shown that elevated biomarkers and right ventricular (RV) dysfunction have been associated with increased risk of mortality. Therefore, aggressive treatment is necessary to "unload" right ventricle. The treatment of submassive PE with thrombolysis is controversial, though recent data have favored thrombolysis over conventional anticoagulants in acute setting. The most feared complication of systemic thrombolysis is intracranial or major bleeding. To circumvent this problem, a newer and safer approach is sought. Ultrasound-accelerated thrombolysis is a relatively newer and safer approach that requires local administration of thrombolytic agents. Herein, we report a case series of five patients who underwent ultrasound-accelerated thrombolysis with notable improvement in symptoms and right ventricular function.